Sustainable food management systems in pesantren - Nuryana Zalik; Haryadi Hari; Rahman Arif; Ichsan Yazida; Saifuddin Much Fuad; Aziz Muhammad Thariq; Herdian (BIO Web of Conferences)
Pesantren, Islamic boarding schools in Indonesia, play a crucial role in the education and well-being of students, making the implementation of sustainable food systems vital for enhancing food security and nutrition. This study aims to provide a comprehensive bibliometric analysis of sustainable food management systems in pesantren using data from the Scopus database. A total of 112 documents were analyzed using VOSViewer to visualize publication patterns, authorship, research trends, and collaboration networks. The results reveal significant contributions from various countries and institutions, with the United States leading in both publications and citations. The analysis also highlights key thematic clusters, including food security, nutrition, and sustainability. The study concludes that while there is growing academic interest in sustainable food systems in pesantren, specific research gaps remain, particularly regarding the integration of pesantren-specific contexts. This research contributes to the understanding of sustainable food practices in educational settings and provides insights for policymakers, educators, and community leaders to develop effective strategies for sustainable development and health promotion in Indonesia.